The Rise of Rural Industrialization in China with Special Reference to Non-agricultural Development: A Case Study from Guangxi - Feng, Haying; Squires, Victor (Advances in Social Sciences Research Journal, 2022)
In recent years, rural transformation has gradually become the focus of scholars and Governments in the context of global sustainable development; it is of great significance to achieve urban-rural integration and coordinated development through studying the spatial-temporal characteristics and driving mechanism of rural transformation development. The ultimate purpose of our study, which is part of an ongoing major research agenda at the Qinzhou Development Institute within the Bei Bu Gulf University is to better understand the origins of, and trends in, the expansion of rural Industrialization. We focused on south-west China – a region much influenced by the Belt and Road initiative. We reviewed the existing literature on rural industrialization and attempted to explore the advantage of rural over urban industries based on the results of case studies in China (mainly pertaining to the coastal zones of the Yangtze and Pearl river deltas). We examined the crucial characteristics of rural enterprises and entrepreneurs based on micro-level evidence from Guangxi and neigbouring provinces.